Efficacy of Post-Operative Logbook-Based Quadriceps Exercises on Functional Outcome after Total Knee Arthroplasty - Ongkosit, Chatchapol; Panuwet, Ruengsiri (Journal of Southeast Asian Orthopaedics, 2023)
Purpose: Most patients who undergo total knee arthroplasty (TKA) are elderly. Some patients have recognition impairments and cannot correctly perform home-based rehabilitation effectively. This study aimed to compare the functional outcomes between logbook- and non-logbook-based quadricep exercises. Methods: In this prospective cohort study with retrospective case controls scheduled for unilateral primary/bilateral TKA, we compared 57 patients who received post-operative home-based rehabilitation and seated knee extension exercises (non-logbook group) with 60 patients who received the same protocol but were provided a logbook with paper handouts containing the schedule, date, time, and record form (logbook group). The modified Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores and data pertaining to range of motion (ROM) were collected pre-operatively and at 6, 12, and 24 weeks post-operatively. Results: The logbook group showed a significant improvement in the mean difference in function and total WOMAC scores at 6-weeks post-operatively (p < 0.05). There was no significant difference in the pre- and post-operative ROM at any follow-up time point between the groups. Conclusions: Logbook-based quadriceps exercises resulted in significant early improvement in the functional outcomes. Logbooks may help patients who have undergone TKA to perform their home-based exercise regimens accurately.